Experience of managing menopausal symptoms and quality of sleep with melatonin - E. V. Bryukhina; E. N. Usoltseva; D. I. Burchakov (Медицинский совет, 2016)
Melatonin is one of the most underestimated agents of the endocrine system. While remaining undeservedly in the shadow of clinical science, it adjusts the body to the systemic changes of the external and internal environment. The periods of perimenopause and menopause are characterized by high levels of stress and reduced quality of life. In recent years, there is a growing understanding that melatonin as adaptogenic hormone supports the female body in this particularly vulnerable period of life. We assessed secretion of melatonin in women with climacteric syndrome (CS) and the effect of melatonin therapy on menopausal symptoms and quality of sleep. The study involved 31 women (mean age 53.5 ± 4,1 years) with mild CS (average age of menopause 52 ± 3 years). Melatonin secretion was evaluated by the concentration of its metabolite (urinary 6-hydroxy-melatonin-sulfate) using enzyme immunoassay. All patients received melatonin 3 mg/day orally at bedtime for 3 months. The results of the treatment were clinically assessed using the modified menopausal index (MMI) and the Pittsburgh Sleep Quality Index (PSQI). We found that baseline 6-hydroxy-melatonin-sulfate levels were very low in the evening urine: 1.88 ng/ml (1.08 to 5.34); at night and in the early morning they moderately increased (up to 6.36 ng/ml [from 2,34 to 16,04] and 25.71 ng/ml [15.51 to 32.03], respectively). After 1 month of treatment, MMI in the subjects decreased from 24,9 ± 8,1 points to 16,6 ± 8,8 (P = 0.013) and further to 13,2 ± 6,3 points after 3 months (P = 0.001). The MMI demonstrated a significant decrease of neuro-vegetative symptoms. The median PSQI decreased from 9 to 2 points (p = 0,027). Our findings suggest that melatonin is able to inhibit mild CS and the associated sleep disturbances.